2022
DOI: 10.15294/harmonia.v21i2.32243
|View full text |Cite
|
Sign up to set email alerts
|

Idris Sardi’s Influence on Musical Development and Education in Indonesia

Abstract: Idris Sardi is known as a music maestro in Indonesia. This study aims to reveal the influence of Idris Sardi on the development of music and its implications in music education. This study uses a qualitative method with a narrative approach. The data were collected through observation, in-depth interviews, and documentation. The research informants were carefully selected from the family, violin students, and colleagues of Idris Sardi in Jakarta and Bogor, West Java. The data were analyzed by organizing data a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…The development of song media as part of activities that are closely related to music. Music has become an important part of human life (Wan & Schlaug, 2010;Fuadi, Sudira & Astuti, 2021;Andrew et al, 2022;Husna, & Rinjani, 2022)). Various religions such as Christianity and Islam use music to support worship activities to God, the Creator of the Universe (Mazokopakis, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The development of song media as part of activities that are closely related to music. Music has become an important part of human life (Wan & Schlaug, 2010;Fuadi, Sudira & Astuti, 2021;Andrew et al, 2022;Husna, & Rinjani, 2022)). Various religions such as Christianity and Islam use music to support worship activities to God, the Creator of the Universe (Mazokopakis, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The implementation of students' aesthetic development takes place through diverse approaches, models, strategies, methods, and techniques. Fuadi, Sudira, and Astuti(2021) stated that concept of music learning models include problem-based learning, capacity building, and life-based learning. Meanwhile, Astuti et al (2022) found that focusing on music learning can be done in various ways, including imitation.…”
Section: ⅰ Introductionmentioning
confidence: 99%
“…The work ability of each individual which includes aspects of knowledge, skills, and work attitudes is a general definition of competence. According to Fu'adi et al, (2022) which states that competence is an individual's ability to carry out a job correctly and has advantages based on matters relating to knowledge, skills, and attitudes.…”
Section: Introductionmentioning
confidence: 99%
“…This is then able to support the organization to achieve its goals effectively and efficiently.The work ability of each individual which includes aspects of knowledge, skills, and work attitudes is a general definition of competence. According toFu'adi et al, (2022) which states that competence is an individual's ability to carry out a job correctly and has advantages based on matters relating to knowledge, skills, and attitudes.In a competency, an employee must have several existing elements, according to the opinion of Gunara & Sutanto, (2021), namely: 1) Expertise (Having expertise in accordance with the field of work mastered); 2) Knowledge (To support work, have the will to increase knowledge); and 3) Attitude (Have initiative in helping co-workers, have friendliness and courtesy in carrying out work and respect for a complaint).The competence of each person has an important role in the effectiveness of the implementation of various work tasks, according to the opinion Tjabolo, (2020) explaining that there have been many benefits of having competence in organizations, namely to clarify a work standard, to select potential workers, to maximize the productivity of a company/organization. , develop a remuneration system, and balance work behavior with the rules contained in a company/organization Suharno et al, (2020).…”
mentioning
confidence: 99%